2010
DOI: 10.5301/jn.2010.2020
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-7 expression is down-regulated in human clear cell renal carcinoma

Abstract: 2 ABSTRACTRecent studies demonstrated that the expression pattern of bone morphogenetic protein 7(BMP-7) is altered in different tumors. We determined expression of BMP-7 in human clear cell renal carcinoma (CCRC).Samples from cancer and corresponding healthy tissue were obtained from 20 patients who underwent nephrectomy for CCRC. Expression of BMP-7 mRNA was determined by RT-PCR and protein expression was analyzed by immunohistochemistry.RT-PCR showed strong downregulation of BMP-7 mRNA in cancer tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…We found higher expression of BMP7 in the RCCs than in the normal tissue, and BMP7 expression was lost in CC-RCCs with higher tumor stage. Thus, our results are partly in concordance with the recent study which reported BMP7 mRNA expression and protein were downregulated in CC-RCC [18]. Kwak et al [14] have reported that the BMP7 protein expression rate in NCC-RCC was higher than that in the CC-RCC.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found higher expression of BMP7 in the RCCs than in the normal tissue, and BMP7 expression was lost in CC-RCCs with higher tumor stage. Thus, our results are partly in concordance with the recent study which reported BMP7 mRNA expression and protein were downregulated in CC-RCC [18]. Kwak et al [14] have reported that the BMP7 protein expression rate in NCC-RCC was higher than that in the CC-RCC.…”
Section: Discussionsupporting
confidence: 83%
“…It has also been found that the BMP signaling pathway is involved in tumorigenesis and can be used as molecular targets for cancer therapy. BMPs have hardly been investigated in human renal cell carcinomas (RCCs) and most of the published studies have explored BMP4, BMP6 and BMP7 [14][15][16][17][18].…”
mentioning
confidence: 99%
“…In keeping with this, data from the MTT cell proliferation assay showed no differences in cell viability and proliferation between control and A549 cells. BMP7 has been indicated to act as a mediator/regulator of cell survival and apoptosis in several tumour cell lines (3,(6)(7)(8)13,25,26,27), including prostate cancer cells, colon cancer cells, breast cancer cells and melanoma cells and renal cancer cells. In the present study, our results from the apoptosis assay showed that BMP7 offers no significant protection against apoptosis in the tumour cells transfected with BMP7 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TGF-β/BMP proteins is most commonly regulated at the mRNA level. As an example, this is particularly evident in BMP-7 where changes in Bmp7 mRNA expression occur following renal injury (Simon et al, 1999) and during tumorigenesis (Basic-Jukic et al, 2011). While the mechanisms regulating Bmp7 transcription are poorly understood, the Bmp7 promoter has been cloned and shown to contain numerous putative transcription factor binding sites (Dorai et al, 2001;Simon, Feliers, Arar, Bhandari, & Abboud, 2002).…”
Section: Ligand Expressionmentioning
confidence: 97%